Potential Utilization of Defective Fruit Juice Products for Black Soldier Fly Cultivation to Reduce Waste Generation in the Beverage Industry - Syah, Fikri Nur Rahman; Sari, Gina Lova (Journal of Community Based Environmental Engineering and Management, 2024)
The waste of fruit juice and tea defective products has organic content that conventionally has the potential to be utilized as a medium or place for maggot growth, but until now it has not been equipped with supporting scientific studies. Therefore, the objectives of the study are: 1) Assessing the characteristics of fruit juice and tea product waste, 2) Assessing the effectiveness of maggot in reducing fruit juice and tea product waste. This research is experimental in nature using variations in the composition of fruit juice and tea product waste as a source of nutrition for maggot which is carried out for 12 days. This variation uses the Complete Randomized Design method with 3 (three) treatments, namely variations in the composition of 60% tea + 40% fruit juice waste (S1), 50% tea + 50% fruit juice waste (S2), and 40% tea + 60% fruit juice waste (S3) in duplo. In addition, this study was completed with a control treatment. The results showed that the characteristics of fruit juice and tea waste containing protein (3.78-4.59%), fat (0.90-1.31%), carbohydrates (28.15-29.15%), crude fiber (2.42-3.12%) can be used as maggot cultivation media. The highest protein and crude fiber contents were found in the S3 composition waste at 4.59% and 3.12%. Maggot cultivation results that showed the highest fat and carbohydrate content were found in S1 composition waste at 1.31% and 29.15%. The recommended composition variation is S1 composition with the highest substrate consumption value and waste reduction index of 57.47% and 20.06%.